PERANCANGAN APLIKASI JEJARING SOSIAL ALUMI PENCINTA APLIKSI BERBASIS ITC DENGAN ALGORITMA GRAPH BERBASIS WEB - Fitri Latifah; Imam Saefudin (PETIR, 2018)
Alumni is a person who finished their studi from colege or university. Alumni STMIK Nusa Mandiri or commonly referred to as IKANI has an important role in showing the imaging and quality of a university, because the alumni container is not just a forum of friendship between alumni, but also a container to counsel and communicate efforts and efforts in advancing university. By utilizing the internet facility then created a social networking site for alumni STMIK Nusa Mandiri which can facilitate communication between the alumni. Communicating using this site can make friendship and knowledge in teh ITC, become closer than other site which already axist in Internet. This site was created by starting the first system design using UML then continued with the creation of user interface and by using programming language PHP and MySQL as database management. The site still has some disadvantages in terms of both features and security.